“Adequate dose” in the drug treatment of mental disorders - V. L. Kozlovskii; N. V. Kozlovskaya; D. N. Kosterin; O. V. Lepik; M. Yu. Popov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2023)
The article discusses the use of different doses of psychotropic drugs in the treatment of mental disorders. It is known that the number of responders is about two thirds of all patients, which according to the “three sigma” rule for the normal distribution of cases, fits into the range of one sigma. The hypothetical calculation of the relative proportions of patients responding to treatment in low, mid-range and high doses is given. In accordance with this, the use of a mid-range treatment doses is justified, thereby the number of potential responders increases almost twice as compared with the use of small doses. Within the framework of pharmacodynamics, the probability of the development of dose-dependent effects is assessed, including both desirable and untoward effects of various pharmacological classes of psychotropic drugs in different doses.